2017
DOI: 10.37358/rc.17.9.5826
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac Influence on Photosynthetic Parameters and Volatile Organic Compounds Emision from Phaseolus vulgaris L.Plants

Abstract: Diclofenac, both from human and veterinary consumption, may arrive in landfills or in the wastewater treatment plants, becoming an environmental pollutant. Therefore, we aimed to study the influence of diclofenac on plants growth and development. We chose as model plant the bean (Phaseolus vulgaris L.) that was watered with different concentrations of aqueous diclofenac solutions (0-0.4 g/L). The plants exhibited linear decreased values of net assimilation rates and stomatal conductance to water vapors with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…However, after 4 years of regulation and numerous media campaigns, aimed at raising the awareness among the population about the effects of drug pollution, the collection is still difficult and there are still pharmacies that refuse to take medicines from the population under different pretexts. The latest studies carried out in our country have indicated the presence of a large number of pharmaceutical compounds in the Danube waters [47], important rivers [15], soil [48], and plants [49][50][51][52]. This context calls for more in-depth studies on issues related to the management of pharmaceutical waste in Romania.…”
Section: Introductionmentioning
confidence: 99%
“…However, after 4 years of regulation and numerous media campaigns, aimed at raising the awareness among the population about the effects of drug pollution, the collection is still difficult and there are still pharmacies that refuse to take medicines from the population under different pretexts. The latest studies carried out in our country have indicated the presence of a large number of pharmaceutical compounds in the Danube waters [47], important rivers [15], soil [48], and plants [49][50][51][52]. This context calls for more in-depth studies on issues related to the management of pharmaceutical waste in Romania.…”
Section: Introductionmentioning
confidence: 99%
“…On a global scale, it is estimated that around 10 billion tonnes of soil is eroded annually through natural processes, but man-made erosion is 2.5 times more intense -26 billion tonnes/year. This phenomenon is a direct consequence of the inappropriate exploitation of the soil, but also of its pollution.Anthropogenic activities such as industrial, mining, agricultural and household, and the inappropriate disposal of wastes result in the accumulation of some pollutants in the soil surface, causing serious damage to the environment [5][6][7][8][9].In the last decades, the quantities of fertilizers used in agriculture [10] have increased considerably.This can lead to the alteration and deterioration of soil properties and structure [11,12], with direct consequences on the quality and quantity of active and nutritive principles in grown plants [13][14][15][16][17][18][19][20][21][22]. Romania has a long history of mining useful substances such as gold, copper, lead, zinc, silver, manganese, salt and coal.However, due to the deplorable years of exploitation of the environment and mineral extraction technologies, mines and related ore processing industries have affected the environment in a negative way, resulting in an important burden on the water, air and soil of ecosystems [3,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The contamination of water supplies happens for many reasons. Some are related to human activities and population growth rate as: use of irrigation, agriculture, chemical fertilizers, rotation of crops [3][4][5][6][7][8][9], industrial sector [10,11], local activities as anthropogenic sources (transportation and highways) [12], water distribution networks [13], organic waste or infiltrations from sewage treatment plants [5,[14][15][16], in a few words mismanagement of water resources [17,18]. Some are related to natural hazard: geochemical composition of the rocks [4,19], accidental weather phenomena [20,21].…”
mentioning
confidence: 99%